Validity of the Stick-Biting Test for Diagnosis of Patients with Temporomandibular Disorders - Shigeta, Yuhko; Kondoh, Toshirou; Ogawa, Takumi; Fukushima, Shunji; Hirai, Shinya (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Purpose: In this study, the stick-biting test was applied to temporomandibular disorders (TMD) patients, and the responses were compared with disc conditions combined with pain at clinical examination. The purpose of this study was to clarify the diagnostic accuracy of this test for diagnosing disc displacement with pain at clinical examination. Methods: Subjects were selected from patients who visited either the prosthetic or the oral and maxillofacial departments at Tsurumi University Dental Hospital and were diagnosed as having TMD. They were asked to clench unilaterally on a plastic stick (about 9mm thick) placed at the most posterior portion on the dentition. Then, the site and amount of evoked pain were recorded. Those findings were related to MRI findings combined with pain at clinical examination; that is, no disc displacement (N), disc displacement without pain (NP-Dis), and disc displacement with pain (PDis). Results: Pain on the non-clenching side was mostly evoked at the TMJ region, and their disc conditions were chiefly in P-Dis. The diagnostic accuracy of this test for this phenomenon was: efficiency, 83%; sensitivity, 71%; specificity, 89%; positive predictive value, 76%, and negative predictive value, 86%. Conclusions: It was suggested that pain in the contralateral-side TMJ region during the stick-biting test was useful to clinically identify painful disc displacement at clinical examination with high diagnostic accuracy.